The application of the transtheoretical model to identify physical activity behavior in women - Asiyeh Pirzadeh; Firoozeh Mostafavi; Fazlollah Ghofarnipour; Marjan Mansourian (Wolters Kluwer Medknow Publications, 2017)
Background: The low level of physical activity is a risk factor behind several chronic diseases. Evidence shows the level of physical activity is decreasing, especially in women. This study aimed to apply the transtheoretical model to identify physical activity behavior in women who referred to health centers of Isfahan. Materials and Methods: This cross-sectional study was carried out among 400 women in Isfahan's health centers. Data were collected using a questionnaire including demographic factors, the standard of exercise behavior, stages-of-change questionnaire, processes of change, self-efficacy, and decisional balance. Data were analyzed with the Statistical Package for the Social Sciences (SPSS) (version 16). Descriptive statistics, the Mann-Whitney test, one-way analysis of variance (ANOVA), and Pearson correlation were used. Results: The mean (SD) of age was 31.46 (8.92); 81.5% of women were housewives and the others employees. The mean score of physical activity per day for women was 10.66 min. Ninety-six persons (24%) were classified in the pr-contemplation stage, 100 (33.3%) in the contemplation stage, 102 (25.5%) in the preparation stage, 29 (7.2%) in the action stage, and 40 (10%) in the maintenance stage. The results showed the stages of change significantly correlated with the decisional balance (P = 0.04), processes of change, and self-efficacy (P < 0.01). Conclusions: With regard to the low level of physical activity in women and the role of the stages-of-change model in determining effective factors behind behavior, there should be an attempt to develop continuous and organized educational programs to promote physical activity in women by using the transtheoretical model.